Q: A compound experiment consists of drawing at random twice without replacing from a jar with 3 red, 3 white, and 2 black marbles. What is the probability of getting first a red and then a black

marble? A.3/28 B.3/32 C.1/4

A: A compound experiment consists of drawing at random twice without replacing from a jar with 3 red, 3 white, and 2 black marbles. -A.3/28

Expert answered|bestWeegy|Points 460|

Rating

There are no new answers.

Find the slope of the line that passes through the points (0, 0) and (-2, -3).
A.2/3
B.3/2
C.-3/2
**Weegy:** Simplifying
Ax + By = C
Solving
xA + yB = C
Solving for variable 'x'.
Move all terms containing x to the left, [ [ all other terms to the right.
Add '-1yB' to each side of the equation.
xA + yB + -1yB = C + -1yB
Combine like terms: yB + -1yB = 0
xA + 0 = C + -1yB
xA = C + -1yB
Divide each side by 'A'.
x = A-1C + -1yA-1B
Simplifying
x = A-1C + -1yA-1B ] ] (More)

Question

Expert Answered

Updated 1/28/2014 2:45:52 PM

1 Answer/Comment

The slope of the line that passes through (0, 0) and (-2, -3) is:

3/2

3/2

Added 1/28/2014 2:45:50 PM

This answer has been confirmed as correct and helpful.

Find the slope of the line that passes through the points (3, 6) and (5, 3).
A.-3/2
B.3/2
C.2/3

Question

Not Answered

Updated 7/28/2014 1:22:28 PM

1 Answer/Comment

Find the slope of the line that passes through the points (3, 6) and (5, 3). A.-3/2 B.3/2 C.2/3
**Weegy:** A.-3/2 (More)

Question

Expert Answered

Updated 16 days ago|11/4/2017 8:39:39 AM

1 Answer/Comment

The slope of the line that passes through points (3, 6) and (5, 3) is -3/2.

m = (3 - 6)/(5 - 3)

m = -3/2

m = (3 - 6)/(5 - 3)

m = -3/2

Added 16 days ago|11/4/2017 8:39:39 AM

This answer has been confirmed as correct and helpful.

standard form the equation of the given line. The line that passes through (-2, 4) and is parallel to x - 2y = 6
**Weegy:** The answer is y=(x)/(2)+5. [ Here is the steps for solving such a problem: x-2y=6_(-2,4)
Since x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting x from both sides.
-2y=-x+6
Divide each term in the equation by -2.
-(2y)/(-2)=-(x)/(-2)+(6)/(-2)
Move the minus sign from the denominator to the front of the expression.
-(-(2y)/(2))=-(x)/(-2)+(6)/(-2)
Multiply the factor by the rest of the expression to remove the fraction from the denominator. To multiply by a factor in the denominator, multiply by 1 over the factor.
-*-(2y)/(2)=-(x)/(-2)+(6)/(-2)
Cancel the common factor of 2 in -(2y)/(2).
-*( 2 y)/( 2 )=-(x)/(-2)+(6)/(-2)
Remove the common factors that were cancelled out.
-*-y=-(x)/(-2)+(6)/(-2)
Multiply - by -y to get y.
y=-(x)/(-2)+(6)/(-2)
Move the minus sign from the denominator to the front of the expression.
y=-(-(x)/(2))+(6)/(-2)
Multiply the factor by the rest of the expression to remove the fraction from the denominator. To multiply by a factor in the denominator, multiply by 1 over the factor.
y=-*-(x)/(2)+(6)/(-2)
Multiply - by -x to get x.
y=(x)/(2)+(6)/(-2)
Move the minus sign from the denominator to the front of the expression.
y=(x)/(2)-((6)/(2))
Multiply the factor by the rest of the expression to remove the fraction from the denominator. To multiply by a factor in the denominator, multiply by 1 over the factor.
y=(x)/(2)-(6)/(2)
Cancel the common factor of 2 in -(6)/(2).
y=(x)/(2)-(^(3) 6 )/( 2 )
Remove the common factors that were cancelled out.
y=(x)/(2)-3
To find the slope and y intercept, use the y=mx+b formula where m=slope and b is the y intercept.
y=mx+b
Using the y=mx+b formula, m=(1)/(2).
m=(1)/(2)
To find an equation that is parallel to x-2y=6, the slopes must be equal. ] (More)

Question

Expert Answered

Updated 10/25/2011 12:22:23 AM

3 Answers/Comments

y=(1/2)x+6 is the standard form equation of the line that passes through (-2, 4) and is parallel to x - 2y = 6.

Added 10/24/2011 12:27:23 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/22/2014 4:01:26 PM]

How can you rate me bad when the answer is correct. What is would be the standard form...

Added 10/24/2011 8:22:27 PM

@thederby the standard form is y=mx+b so the correct equation should be y=(1/2)x+6, where m=1/2 and b=6. your answer y=(x)/(2)+5 is incorrect. the y-intercept "b" should be equal to 6 not 5. ref:

Added 10/25/2011 12:22:23 AM

26,490,793 questions answered

There are no comments.